OPTIMALISASI PENGELOLAAN DATA TANAH MENGGUNAKAN ARCGIS DI BADAN BANK TANAH - Andi Rukmana; Angger Styo Yuniarti; Samsul Makin; Muhammad Arif Kurniawan; Ferdi Kuswandi (LPPM UNIVERSITAS INSAN PEMBANGUNAN INDONESIA, 2025)
Badan Bank Tanah, which is primarily engaged in the land sector, requires technology that can manage maps centrally and can be used collaboratively with both internal and external providers through service connections to support analysis and monitoring of HPL assets by related stakeholders based on the level of access provided. Currently, Badan Bank Tanah does not have a centralized GIS system, the process of creating shape files and map polygons is still carried out by each staff. This results in the information, database types, and data structures created being non-standard, and results in the shape file and map polygon databases being stored on each staff's work tools. The risk that can occur from this is the loss or misinformation needed, so that if needed, it takes time to prepare the data. The solution to the application being sought is software that has the capability to store data in a standardized manner, can be connected to external GIS applications through service methods, and is centralized so that the data can be stored in a secure environment